The Development Of Biology Modul With LKS Orientation Problem Based Learning (PBL) In Topic Environmental Pollution For Grade X - Ramadhan Sumarmin; Desfira Mustika Ayu; Lufri Lufri (Bioeducation Journal, 2018)
Based on the observation done by the writer in Don Bosco senior high school on the odd and even semesters during 2011 concluded that teachers, in general, do not use the biology learning at the class completely. The module of biology is only available in the odd semester but not in the even semester. The process of learning that takes place during the time in school just using the textbook or handouts made by teachers in the study. Meanwhile, the textbook is available at the school are less varied. During this time the students are taught using textbooks that contain the material at length content and tend to use convoluted sentences. Moreover, the picture presented is also less communicative and sometimes has no relation with the text, so students are difficult to understand the material presented. The purpose of this study is to produce a biology module that is completed by student worksheet and oriented to the problem based learning (PBL) are valid, practical and effective on environmental pollution topics. This research is categorized as research and development. The model and procedure of this research apply 4-D (four-D models) that consists of define, design, develop, and disseminate stage. The results of this research show that the biology module that is completed by student worksheet and oriented to the problem based learning (PBL) is effective, it can be seen from the activity, motivation and students’ learning outcomes. It is concluded that the biology module which is completed with student’s worksheet and oriented to the problem based learning (PBL) on the matter pollution is stated very valid, practical and effective.